Semantic indexing and hyperlinking of multimedia news: The RitroveRAI system - Basili, R.; Cammisa, M.; Donati, E.; Moschitti, A. (Journal of Digital Information Management, 2006)
Web services tend to offer functional and non-functional requirements and capabilities in an agreed, machine-readable format. The target is to provide automated services for discovering, selection and binding of information as a native capability of middleware and applications. However, the major limitations are due to the lack of clear and processable semantics. In this paper, a system, RitroveRAI, addressing the general problem of enriching a multimedia news stream with semantic metadata is presented. News metadata are explicitly derived from transcribed sentences or implicitly expressed into a topical category automatically detected. The enrichment process is accomplished by aligning individual audiovisual segments with news or journal articles reachable trough the Web. This distributed process designed for RitroveRAI enables several extensions in light of large scale and public access performance as suggested in the discussion of the evaluation results of our current system.
Keywords: Hyper link structure; Meta data; Multimedia indexing; RitroveRAI; Semantic web; Web services